A biomechanical approach to evaluate overload and specificity characteristics within physical preparation exercises. Issue 10 (18th May 2020) - Brazil, Adam; Exell, Timothy; Wilson, Cassie; Irwin, Gareth
ABSTRACT: An essential component of any physical preparation programme is the selection of training exercises to facilitate desired performance outcomes, with practitioners balancing the principles of sports training to inform exercise selection. This study aimed to advance biomechanical understanding of the principles of overload and specificity within exercise selection, utilising novel joint kinetic and intra-limb joint coordination analyses. Three-dimensional kinematic and kinetic data were obtained from six male sprinters (100 m PB, 10.64–11.00) performing block starts (competitive motor task) and seven training exercises that encompassed traditionally viewed general and more specific exercises. Results highlighted the challenging nature of exercise selection, with all exercises demonstrating capacity to overload relevant joint kinetic features of the block start. In addition, all exercises were able to promote the emergence of proximal and in-phase extension joint coordination patterns linked with block start execution, although traditionally viewed non-specific exercises elicited greater overall coordination similarity. The current research helps advance biomechanical understanding of overload and specificity within exercise selection, by demonstrating how exercise selection should not solely be based on perceived replication of a competitive motor task. Instead, practitioners must consider how the musculoskeletal determinants of performance are overloaded, in addition to promoting task specific coordination patterns.